2015
DOI: 10.3168/jds.2015-9576
|View full text |Cite
|
Sign up to set email alerts
|

Supplementation with difructose anhydride III promotes passive calcium absorption in the small intestine immediately after calving in dairy cows

Abstract: The incidence of hypocalcemia increases in high-parity dairy cows because resorption of bone Ca is delayed in these animals, and they appear to have a reduced ability to absorb Ca from the intestine during the early postpartum period. Difructose anhydride (DFA) III has been shown to promote the absorption of intestinal Ca via a paracellular pathway. However, past studies have not reported this effect in peripartum dairy cows. Therefore, we investigated the effect of DFA III supplementation on Ca metabolism dur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0
3

Year Published

2016
2016
2021
2021

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 18 publications
(19 citation statements)
references
References 53 publications
0
16
0
3
Order By: Relevance
“…Wynn, Teramura, Sato, and Hanada () demonstrated that serum Ca concentrations after calving were positively associated with the rumen contraction frequency and DMI after calving. Although there was no significant difference in the serum Ca concentration at 3 days after calving between the first lactation heifers and the multiparous cows, the serum Ca concentration generally tends to be low in high parity cows (Teramura et al., ; Wynn et al., ). First lactation heifers can maintain serum Ca at steady concentrations without any treatments after calving because low parity cows absorb Ca efficiently, owing to active mechanisms of Ca homeostasis, including Ca absorption from the intestine and bone resorption (Bronner, ; Goff, Reinhardt, & Horst, ; Kamiya, Kamiya, Tanaka, & Shioya, ).…”
Section: Resultsmentioning
confidence: 99%
“…Wynn, Teramura, Sato, and Hanada () demonstrated that serum Ca concentrations after calving were positively associated with the rumen contraction frequency and DMI after calving. Although there was no significant difference in the serum Ca concentration at 3 days after calving between the first lactation heifers and the multiparous cows, the serum Ca concentration generally tends to be low in high parity cows (Teramura et al., ; Wynn et al., ). First lactation heifers can maintain serum Ca at steady concentrations without any treatments after calving because low parity cows absorb Ca efficiently, owing to active mechanisms of Ca homeostasis, including Ca absorption from the intestine and bone resorption (Bronner, ; Goff, Reinhardt, & Horst, ; Kamiya, Kamiya, Tanaka, & Shioya, ).…”
Section: Resultsmentioning
confidence: 99%
“…Because the concentration gradient absorption is a characteristic of a paracellular pathway, some IgG could have been absorbed through the paracellular pathway. It has been reported that DFA III enhances the opening of intestinal epithelial tight junctions (Mineo et al, 2002) and thereby increases mineral absorption in cattle (Teramura et al, 2015b). Teramura et al (2015a) reported that DFA III enhances calcium absorption through the paracellular pathway of everted bovine intestinal sacs.…”
Section: Discussionmentioning
confidence: 99%
“…Taylor et al (2009) reported a similar result using serum deoxypyridinoline (DPD), as the inhibition of bone resorption had continued around parturition. Devkota et al (2015) revealed the increase in the number of bone-resorbing cells before parturition; on the other hand, Teramura et al (2015) found the acute decline of the serum crosslinked N-telopeptide of type I collagen (NTx) on the day of calving.…”
Section: Figurementioning
confidence: 99%